Comparison Between Exclusively and Non-Exclusively Breastfed Infants for the Development of Acute Respiratory Infections and Diarrhe - Zeb, Faiza; Amjad iqbal; Muhammad Fahad; Saad Ateeq (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the incidence of acute respiratory infections (ARI) and diarrhea in exclusively breastfed infants versus those not exclusively breastfed from the second to the sixth month of life.Study Design: Prospective observational study.Place and Duration of Study: Pediatrics Department of Combined Military Hospital, Abbottabad, Pakistan from Jul 2024 to Jan 2025.Methodology: Infants were divided into Group-A (n=260), who were exclusively breastfed and Group-B (n=260), who were non-exclusively breastfed. Infants were followed up for feeding habits and incidence of ARI and diarrhea from the 60th till the 180th day of life. Primary variables studied were the incidence of ARI and diarrhea during the duration of the study protocol. Odds ratio was calculated for the same.Results: Incidence of ARI was seen in 72(27.7%) infants in Group-A versus 133(51.2%) infants in Group-B (p